Doctoral Programs in Educational Leadership: A Duality Framework of Commonality and Differences - Perry A. Zirkel (Educational Considerations, 2012)
In recent years, doctoral programs in education leadership have been subject to notable criticism and proposals for reform.
Keywords: doctoral; national movement; education; programs; reform; schools; frame work; leadership; professional; practice